Health intervention trials involving transgender, transabled and transracial persons in Africa: A scoping review - Amzat, Jimoh; Kanmodi, Kehinde Kazeem; Aminu, Kafayat; Ismail, Abbas; Salami, Afeez Abolarinwa (Public health challenges, 2024)
Background Health intervention trials constitute important research efforts to find appropriate solutions to health issues affecting different populations. In many cases, it involves high‐risk groups such as the trans‐communities. This scoping review aims to review the existing health intervention trials involving transgender, transabled and transracial persons in Africa. Methods This scoping review adopted the research design by Arskey and O'Malley. Using the Population–Concept–Context framework, a robust systematic search of four research databases, including APA PsycINFO, SCOPUS, CINAHL Complete and PubMed, was conducted to retrieve literature relevant to the review's question. Duplicate copies in the retrieved literature were removed using the Rayyan web‐based application. The residual literature was screened for relevance based on the review's inclusion and exclusion criteria, and only those eligible articles were included in this review. From the included literature, data were charted, collated, summarized and presented as results. Results The scoping review included and reviewed only four articles, which reported studies involving transgender persons. No peer‐reviewed original research article on transabled and transracial persons in Africa was found eligible for inclusion in this review. All the reviewed articles focused on at‐risk, healthy and human immunodeficiency virus (HIV)‐uninfected adult participants ranging between the ages of 18 and 65 years. The domains investigated in those articles were on sexual health, HIV preventive drugs and vaccine trials. The reviewed findings showed the use of HIV‐inhibiting medications and HIV screening or testing as vital preventive interventions among transgender persons in Africa. The available research evidence shows sexuality reductionism about trans behaviour by neglecting other health domains. Conclusion Health trial research on transracial, transgender and transabled persons is a largely underexplored research domain in Africa. More health intervention trials, beyond the domain of sexual health, are required to improve the health and well‐being of this highly marginalized population group in Africa. Four articles were included in this scoping review. All the included articles were on intervention trial studies involving transgender persons in Africa; however, none of them investigated transabled and transracial persons. The four articles were about sexual health, HIV preventive drugs and vaccine trials involving transgenders.